Evaluating Active Labour Market Policies Empirical Evidence for Poland During Transition - Puhani, Patrick A. (Physica-Verlag HD, 1999)
Most governments in today's market economies spend significant sums of money on labour market programmes. The declared aims of these programmes are to increase the re-employment chances of the unemployed. This book investigates which active labour market programmes in Poland are value for money and which are not. To this end, modern statistical methods are applied to both macro- and microeconomic data. It is shown that training programmes increase, whereas job subsidies and public works decrease the re-employment opportunities of the unemployed. In general, all active labour market policy effects are larger in absolute size for men than for women. By surveying previous studies in the field and outlining the major statistical approaches that are employed in the evaluation literature, the book can be of help to any student interested in programme evaluation irrespective of the paticular programme or country concerned
Keywords: Labor Economics; Political Science; Econometrics; Labor economics; Political science; Beschäftigungspolitik; Wirtschaftsreform; Wirkungsanalyse; Polen; Hochschulschrift